Economic aspects of government incomes policies - Gardiner, P R G B (School of Economics, 2016)
The purpose of this thesis is to attempt to survey and analyse incomes policies in Western countries which have instituted them and to try to explain the economic problems that confront economies which apply them with the prime object of checking inflation. It is, moreover, important to consider whether the disappointing results flowed from policies which were basically inappropriate for the economies for which they were designed, or whether they were due to a lack of determination by the authorities to carry them out, in view of public hostility towards this kind of government intervention. Incomes policies can, of course, be taken to include many types of direct and indirect government controls and methods of distributing the national product. It is intended, however, to limit the survey to a consideration of their specific objective of controlling inflation, as distinct from their objectives such as reducing the disparity in incomes within a community or the social welfare aspects of pensions and unemployment. We shall, therefore be dealing in the main with incomes policies in the narrower sense "of the relationship between changes in real income and changes in the aggregate of money incomes taking place in the economy at the same".